Performance based on NEMA NU-4 2008 Standard of CDTN/CNEN’s Small Animal PET Scanner - Rodrigo Modesto Gadelha Gontijo; Andréa Vidal Ferreira; Juliana Batista da Silva; Marcelo Mamede (Brazilian Journal of Radiation Sciences)
This study aimed to evaluate the general performance of the preclinical PET scanner (LabPET Solo 4, GE) at CDTN/CNEN using the NEMA NU 4-2008 protocol. The performance parameters include: (i) spatial resolution; (ii) scatter fraction and counts rate performance; (iii) sensitivity and (iv) image quality. For the evaluation specific simulators and a sealed radioactive source of Sodium-22 were used. The results revealed that the NEMA-based radial spatial resolution ranged from 1.79 mm at the center of the FOV to 2.49 mm at a radial offset of 25mm. Tangential resolution ranged from 1.95mm at the center of the FOV to 3.50mm at a radial offset of 25mm. Axial resolution ranged from 1.78mm at the center of the FOV to 5.42mm at a radial offset of 25mm. Iterative image reconstruction improved the radial spatial resolution to 0.93mm at the center of the FOV. For the mouse-sized phantom, the peak noise equivalent count rate (NECR) was 37.8kcps at 85MBq whereas the peak true count rate was 169.9kcps at 125MBq with a count loss of 7.8% for the maximum rate reached at 103.3MBq. The peak of sensitivity (S) and absolute sensitivity (SA) at the center of axial field-of-view (FOV) is 5.7cps.Bq-1 and 0.63%, respectively. The overall imaging capabilities of the scanner were assessed using the NEMA image-quality phantom. The image roughness was 9.5%. Spillover rates (SORs) in air and in water were 0.26 and 0.17 respectively. The recovery coefficients (RCs) were 0.12 for the 1-mm-diameter rod and 0.91 for the 5-mm-diameter rod. The results demonstrate that CDTN/CNENsmall animal PET scanner has adequate reliability and acquired images are compatible with international quality standards for the molecular imaging research.